BTS’s ‘Spring Day’ through the lens of narrative paradigm and semiotics - Sylphania, Decency Ananda; Najah, Shafa Safira; Fatimah, Anggun Nadia (Priviet Social Sciences Journal, 2025)
This study focuses on analyzing the meanings of BTS’s Spring Day music video through the lens of the Narrative Paradigm theory and Roland Barthes semiotics. The study used two primary data collection techniques: observation and literature review. The analysis found nine key scenes showing three stages of emotional transformation: grief, longing, and emotional liberation. Each stage reflects a specific mood, isolation, sorrow, longing, healing, or hope. Additionally, an analysis of eight key lyrics reveals four narrative stages: profound loss and clinging to hope, struggling with normalcy, emerging from despair, and messages of hope and closure. These findings highlight how Spring Day combines visual and lyrical elements to convey the universal message of loss and recovery. BTS’s storytelling on Spring Day offers an emotionally resonant and culturally relevant narrative enriched with semiotic meaning.